(untitled) (CIPEEX, 2025)
The preliminary report is the document by means of which it can attest to the materiality of the drug trafficking offence, under art. 50, § 1 of Law 11.343/06. The said report plays a crucial role as a condition of procedural for the investigation of drug trafficking crime. This document is fundamental in the investigative process and possible denunciation by the Public Prosecutor’s Office in drug trafficking cases. Law no 11.343/2006 (Drug Law) establishes the obligation of this report as a means to prove the illicit nature of the seized substance. Carried out by specialized professionals, the preliminary report aims to identify and attest the nature of the seized substance, verifying whether it is classified as a narcotic or illicit drug according to the legislation. In short, the preliminary finding of narcotic substance not only strengthens the prosecution but also contributes to the formation of a solid evidence base in criminal proceedings. Its importance as a condition of the procedure for the investigation of drug trafficking crime is highlighted in that it provides technical and scientific proof of the illicit nature of the seized substance, essential for due process and the rights of the parties involved.